The Effect of Basal Medium on Callus Induction and Plant Regeneration in Anther Culture of Rice (Oryza sativa L.) - Yoanita Fadlilah Iriani; Dian Catur Prayantini; Hartinio Natalia Nahampun; Retno Mastuti; Nunung Harijati (Postgraduate, University of Mataram, 2025)
Anther culture is an effective tissue culture technique for rapidly producing doubled haploid (DH) plants, significantly shortening the breeding cycle by 2-3 years compared to conventional methods. This study aimed to evaluate the effects of callus induction basal medium (B5 Gamborg and N6 Chu) and subsequent plant regeneration in both Japonica and Indica rice genotypes. The experiment was conducted using a completely randomized design (CRD) with two treatment factors. The first factor was genotype (G), comprising Nipponbare (G1), RCKJ 05 (G2), RCKJ 10 (G3), RCKJ 15 (G4), RCKJ 25 (G5). The second factor was the basal medium (M), consisting of N6 Chu medium (M1) and B5 Gamborg medium (M2). Each treatment combination (genotype x medium) was replicated three times, with one Petri dish (containing 125 anthers) per replicate. Parameters observed included callus induction frequency (CIF), green plantlet regeneration (RGP), and albino plantlet regeneration (RAP). The results demonstrated that both genotype and the basal medium for callus induction significantly influenced callus induction frequency and green plantlet regeneration.